Indigenas Yaguas y Secoyas - Centro de Estudios Teológicos de la Amazonía (CETA) (My University, 1900)
SPANISH: Se observó a un grupo de indigenas entre Secoyas y Yaguas en un desfile vestidos tradicionalmente y tocando instrumentos musiscales bombo y quena.
ENGLISH: A group of indigenous people between Secoyas and Yaguas was observed in a parade dressed traditionally and playing bass drum and quena musical instruments.

SPANISH: Se observó a un grupo de indigenas entre Secoyas y Yaguas en un desfile vestidos tradicionalmente y tocando instrumentos musiscales bombo y quena.
ENGLISH: A group of indigenous people between Secoyas and Yaguas was observed in a parade dressed traditionally and playing bass drum and quena musical instruments.
Yagua and Secoya indigenous people
Keywords: Iquitos (Perú)|~|Native Communities|~|Perú|~|Indigenous or Native populations|~|Musical Instrument|~|Navigation|~|Iquitos (Perú)|~|Comunidades Nativas|~|Perú|~|Poblaciones Indigenas u Originarias|~|Instrumento Musical y Navegación|~|/ Iquitos (Peru)|~|Native Communities|~|Peru|~|Indigenous or Native Populations|~|Musical Instrument and Navigation